Influence of milling media on the properties of some hard metal powders. (April 2021) - Chicinaş, H.F.; Jucan, D.O.; Gădălean, R.V.; Conțiu, G.; Marinca, T.F.; Götze, P.; Eckert, A.; Popa, C.O.
Abstract: This paper presents the results of using an aqueous milling media in comparison with traditional milling routes, as well as the influence of the milling media interaction with powder on the morphology and agglomeration behaviour. Hard Metal powders were milled in four milling media, two of them consisting of traditional milling routes and two of them aqueous routes. The aqueous milled powder is larger in size, similar to acetone and exhibits higher hardness as compared to the powder milled using isohexane, acetone, thus lowering the pressability. The pH adjustment of the water leads to soft agglomerates similar to isohexane and acetone. Powder oxidation occurs after the drying process, being more intense in the case of using an aqueous medium. Using N2 atmosphere has inhibited the powder oxidation for the powder milled in traditional media. Using CO2 or by gradual exposure to air the spontaneous oxidation is prevented for aqueous processing. Graphical abstract: Unlabelled Image Highlights:  tailoring the pH of the aqueous medium leads to friable agglomerates after drying  drying of such powders requires a protective atmosphere based on milling medium  For aqueous milling, drying under slightly oxidising atmosphere gives better results  Aqueous milling can be employed industrially with minor modifications for hard metals